2022
DOI: 10.1039/d2bm00308b
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive hydrogels to deliver reactive species generated by cold atmospheric plasma: a case study with methylcellulose

Abstract: Hydrogels have been recently proposed as suitable materials to generate reactive oxygen and nitrogen species (RONS) upon gas-plasma treatment, and postulated as promising alternatives to conventional cancer therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…However, in the majority of in vitro studies investigating CAP effects, carbohydrates are involved as the primary energy source of cell culture media (5–10 mM) or as gelling agents (% range). 6 , 26 The potential oxidation products may contribute to the observed effects and the subsequent conclusions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the majority of in vitro studies investigating CAP effects, carbohydrates are involved as the primary energy source of cell culture media (5–10 mM) or as gelling agents (% range). 6 , 26 The potential oxidation products may contribute to the observed effects and the subsequent conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported that treating 20 mM of aqueous (D 2 O/PBS) sugar solutions ( d -ribose, d -glucose, and d -sucrose) with air dielectric-barrier discharge plasma (1 mm distance of contact surface) led to a full decomposition into low-molecular-weight organic acids, for example, oxalic, glycolic, tartaric, glyceric, and formic acid. However, in the majority of in vitro studies investigating CAP effects, carbohydrates are involved as the primary energy source of cell culture media (5–10 mM) or as gelling agents (% range). , The potential oxidation products may contribute to the observed effects and the subsequent conclusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, interaction of each individual polymer with CAP should be carefully assessed. To this end, different polymers have been considered to date, including alginate, [ 35 ] gelatin [ 149 ] and their combination, methylcellulose, [ 150 ] polyethyleneoxyde‐based copolymers, [ 161 ] and polyethyleneglycol–polylactide copolymers. [ 162 ] In all cases, RONS were successfully generated within the polymer solutions in a CAP treatment time dependent manner, and the polymers maintained the ability to crosslink and form self‐standing hydrogels (through different crosslinking methods including ionic crosslinking, thermal gelling, or UV crosslinking).…”
Section: Cap Treatment Modalities In Clinicsmentioning
confidence: 99%
“…[ 149 ] In contrast, in CAP‐treated methylcellulose solutions, H 2 O 2 and NO 3 − showed a certain decrease while NO 2 − remained essentially unaltered. [ 150 ] Beside, the crosslinking process could also influence the concentration of RONS initially generated by the CAP treatment. It was reported that for methylcellulose PTH that was gelled thermally, NO 2 − and NO 3 − remained essentially unchanged, but the concentration of H 2 O 2 strongly decreased.…”
Section: Cap Treatment Modalities In Clinicsmentioning
confidence: 99%